2019
DOI: 10.1097/sla.0000000000002665
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Electronic Cardiac Arrest Risk Triage (eCART) Score for Risk Stratification of Surgical Inpatients in the Postoperative Setting

Abstract: Early warning scores are predictive of severe adverse events in postoperative patients. eCART is significantly more accurate in this patient population than both NEWS and MEWS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 16 publications
1
73
1
Order By: Relevance
“…Discrimination by NEWS, as measured by the area under the ROC curve (0.75), was less in our postoperative population than typically reported in acute medical populations (> 0.85). A recent large, single‐centre North American study reported a similar area (0.76) for a general postoperative population . A continuous logistic risk score has previously been demonstrated to offer better discriminatory performance than an additive score in general ward admissions .…”
Section: Discussionmentioning
confidence: 86%
“…Discrimination by NEWS, as measured by the area under the ROC curve (0.75), was less in our postoperative population than typically reported in acute medical populations (> 0.85). A recent large, single‐centre North American study reported a similar area (0.76) for a general postoperative population . A continuous logistic risk score has previously been demonstrated to offer better discriminatory performance than an additive score in general ward admissions .…”
Section: Discussionmentioning
confidence: 86%
“…Most validation of NEWS has been in acute admissions and medical in-patients, settings in which it appears to perform well; there is less validity in elective surgical settings and non-medical specialities. These findings have encouraged researchers to develop specialty-specific scores and, within these subpopulations, the predictive value of a generic EWS suffers in comparison [5,6]. The potential inference is that one standardised EWS may not apply with accuracy to all types of patients and all relevant critical illness events.…”
Section: Validationmentioning
confidence: 99%
“…We saw that cancer patients who experienced IHCA had higher alanine aminotransferase, alkaline phosphatase, and INR on admission. These parameters have been included in several scoring systems that predict cardiac arrest in general floor patients [ 5 ]. Renal and hepatic function tests are available for most patients on admission and these derangements should be given consideration when triaging patients.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic-Cardiac Arrest Risk Triage (e-CART) is a scoring system that incorporates ward vital signs as well as laboratory results and demographics for combined prediction of cardiac arrest, intensive care unit (ICU) transfer, and death [ 4 ]. Multiple studies have validated their use in real-time [ 5 ]. These scoring systems predict the probability of an adverse event in the general patient population and help physicians make timely interventions to prevent cardiac arrest or death.…”
Section: Introductionmentioning
confidence: 99%